The effect of bottom ash replacement as fine aggregate on the property of shotcrete - Sattaya Chaiwithee (2019)
© Int. J. of GEOMATE. This study focused on the effect of the particle size distribution of bottom ash on the engineering properties of shotcrete. Bottom ash was used as fine aggregate replaced fine sand in the mixture of shotcrete. Particle size distribution of aggregate in this test consists of upper boundary and lower boundary of gradation No.1 in ASTM C33 and aggregates passed sieve No.4. The mixture of shotcrete was a combination of Portland cement and fine aggregate is the ratio of 1:3. Water to cement ratio is 0.6. The results demonstrated the compressive strength of shotcrete used bottom ash as an aggregate was less than normal shotcrete approximately 45%. This is due to the particle strength of bottom ash is less than sand. The compressive strength of the samples contains bottom ash passed sieve No.4 gave the highest strength. The compressive strength of the samples contains the lower boundary and upper boundary of gradation No.1 was 7.7 MPa and 10.6 MPa. However, the compressive strength of the samples contains bottom ash passed sieve No.4 was 12.6 MPa. The results of slump flow demonstrated the slump flow of shotcrete tends to increase with the reduction in the particle size of aggregate. Nevertheless, setting time tends to decrease with the reduction in the particle size of aggregate. In conclusion, bottom ash passed sieve No. 4 was the most efficient to use as fine aggregate in the mixture of shotcrete.